Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Produksi UMKM Mukena Mahkota 786 - Oki Devara Farizki; Mila Karmila; Kusuma Agdhi Rahwana (Journal of Management and Creative Business, 2023)
This study aims to determine the effect of work discipline and work environment on employee performance in the production section of UMKM Mukena Mahkota 786. In this study, an associative research method was used using a quantitative approach. The type of data used is primary data and secondary data, with a sample of 49 respondents from production employees at UMKM Mukena Mahkota 786, and using the saturated sample method. The analytical tool used was SPSS version 25. Data collection techniques used interviews and questionnaires. The results of the study show that the Discipline and Work Environment simultaneously have a significant effect on Employee Performance. Work discipline partially has a significant effect on employee performance. The work environment partially has a significant effect on employee performance.